INVESTOR EXPERTISE AND THE RATIONALITY OF DECISION MAKING - Rzeszutek, Marcin; Czerwonka, Monika; Walczak, Magdalena (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
The aim of the paper is to is to explore the determinants of the rationality in decision making among polish stock market investors with different level of expertise with investing. Rationality in decision making was defined from the behavioral finance point of view and was operationalized as the frequency of some behavioral biases (see: the certainty effect) within decision making process. In particular, this study aims to investigate the degree of susceptibility the certainty effect among people of various levels of expertise with investing. As  there is still a lack of data studies in behavioral finance literature investigating the issues mentioned in this article (or existing results are ambiguous) we treated our study as an exploratory research.